The Case of Ditto Block: A Study of Special Weapons and Tactics, Antisocial Personality, Mental Illness and Barricade Offenders - Lichtenwald, Terrance G.; Perri, Frank S. (International Journal of Criminology and Sociology, 2018)
Comprehensive analysis of a repeat barricade offender as part of a Sanity at the Time of Offense evaluation is presented. Sources of information included law enforcement, legal, medical, mental health, and correctional documents from before, during, and after both barricades. Analysis included triangulation of validity interviews from multiple sources against multiple barricade offender databases and research. Incident and offender characteristics at time of barricade one is compared against barricade two. After the first barricade, the offender completed Fitness to Stand Trial restoration, found fit to stand for a jury trial, found not guilty and released. One year later, he was involuntarily admitted to a mental health hospital. Within one week after court-ordered release, the second barricade occurred. During barricade two, the Special Weapons and Tactics team had no intelligence regarding the first barricade. The offender foresaw negotiation strategies and cut off communication. He predicted Special Weapons and Tactic team tactics; he ambushed the team, stalled the entry, retreated, and created a standoff that concluded in a failed suicide by cop incident. Different Third-Party Intermediaries participated in both barricades. During barricade one, the Third-Party Intermediary (his sister) provided intelligence. During barricade two, the Third-Party Intermediary (ex-girlfriend) did not provide intelligence until after the dynamic entry failed, and a team member gathered intelligence from her. Mental health providers never provided intelligence to law enforcement. Analysis reveals Special Weapons and Tactical Teams cannot operate without behavioral specialists. Community leaders’ continuous comprehensive oversight of Special Weapons and Tactical Teams is required for appropriate communication among professionals and policy decisions derived from pattern analysis of Post Incident Reports. Offender risk assessment require law enforcement, corrections, and mental health contributions. Repeat barricade offender scenarios are required components of professional development for Special Weapons and Tactics teams, mental health providers, attorneys, judges, and community leaders.